DEVELOPMENT OF THE VINEYARD CULTIVATION SCHEME FOR THE KAKHETI REGION USING MODERN TECHNOLOGIES. - Manana Kevlishvili; Levan Shavadze (Scholar Express Journal, 2022)
Kakheti is mainly a viticulture-winemaking region, the vineyard areas are growing intensively here. A farmer builds a vineyard according to his opinion without any research, which caused to a reduction of Harvest, All this was reflected in the quality of the grapes and the wine. The reduction in yield was followed by a change in agro-technological measures, deteriorating agro-technological measures led to a reduction in the quality of grapes and wine. In the paper is discussed different schemes of vineyard cultivation, among them has been selected a completer and more cost-effective scheme. The vine feeding area is defined in each scheme, nutrient absorption intensity, is also were determined the chemical composition and growth intensity of the vine shoot in each variant. In the paper was investigated the chemical and mineralogical composition of the obtained grapes. Was made the Wine from grapes obtained from all variants and were determined its chemical composition and quality. The better options for growing vines was allocated and after that was issued recommendations about the vine cultivation scheme.
Keywords: chemical; investigated; recommendations; cultivation